Violencia urbana: La Red Mujer y Hábitat de América Latina (el caso de Colombia) (2017)
This article analyses the international programmes of the Latin American Women and Habitat Network and draws some lines of action for incorporating a rights perspective into the formulation of public policies. The purpose of it is to close the gap that exists between international standards and the reality of women in cities. By juxtaposing feminist concepts and the experiences of the Women and Habitat Network, the need to implement public policies that guarantee the rights of women is discussed. In this sense, the article conceptualises the spaces of the home as part of the city, questions the limits of women's mobility and autonomy and recognises the intersectionality of violence. Revista CIDOB d'Afers Internacionals. © Revista CIDOB d'Afers Internacionals.